Abnormal functional connectivity in psoriasis patients with depression is associated with their clinical symptoms - Wang, Xiaoxu; Liu, Ni; Wu, Lingjun; Zhang, Yanan; Zhang, Guangzhong (Frontiers in Neuroscience, 2022)
Psoriasis is a chronic, autoimmune disorder that is related to mental health disorders such as depression. However, few studies have focused on the features of brain activity in psoriasis patients with depression (PPD) and the association between brain activity and disease severity. A total of 29 PPD and 24 healthy controls were involved in this study, and all participants underwent resting-state functional magnetic resonance imaging (fMRI) scanning. The psoriasis area and severity index (PASI) and the self-rating depression scale (SDS) were used to measure clinical symptoms. Compared with HCs, PPD patients showed increased fractional amplitude of low-frequency fluctuation (fALFF) in the Frontal_Mid_L and increased functional connectivity (FC) between the hypothalamus-R and the Cingulum_Mid_R. Correlation analysis suggested a positive correlation between PASI and SDS scores in PPD, while the fALFF and FC values were negatively correlated with their SDS and PASI scores. These brain regions may be associated with the development of depressive symptoms and disease severity in psoriasis patients.